Improved bake-hardening response of Al-Zn-Mg-Cu alloy through pre-aging treatment. (1st April 2018) - Lee, Yun-Soo; Koh, Dong-Hyeon; Kim, Hyoung-Wook; Ahn, Yong-Sik
Abstract: The effect of pre-aging treatment on the bake-hardening response of an Al-Zn-Mg-Cu alloy was investigated. It was determined that pre-aging immediately after quenching is an effective method to form stabilized Guinier–Preston zones, which can act as precursors to form the metastable η′ phase, and then improve the bake-hardening response. Al-Zn-Mg-Cu alloy sheets pre-aged at 120 °C for 30 min retained high ductility, similar to that of their natural-aged condition, and demonstrated high strength after bake-hardening treatment. Graphical abstract: Image 1